Histochemical and Immunohistochemical Evaluation of the Effects of a Low-Input Diet on Different Chicken Breeds - Elisa Fonsatti; Martina Bortoletti; Marco Birolo; Francesco Bordignon; Gerolamo Xiccato; Angela Trocino; Daniela Bertotto; Marta Vascellari; Giuseppe Radaelli; Cristina Ballarin (Animals)
Reducing the environmental impact of poultry farming aligns with the European Green Deal’s goal of climate neutrality and sustainable food production. Local chicken breeds and low-input diets are promising strategies to achieve this goal. This study evaluated the effects of diet (standard vs. low-input, formulated with reduced soybean meal in favour of local ingredients) on the morphological characteristics of the jejunum in fast-growing chickens (Ross 308), local breeds (Bionda piemontese, BP; Robusta maculata, RM), and their crosses with Sasso (SA) hens (BP × SA, RM × SA). Histological samples from the jejunum were collected at slaughter (47 days for Ross 308, 105 days for others). Jejunal morphology was assessed focusing on villi height, crypt depth, goblet cell density, and immune markers (CD3+ and CD45+ cells). Local breeds, particularly RM, exhibited superior villus height-to-crypt depth ratios, related to better nutrient absorption compared to fast-growing genotypes. Ross chickens had higher goblet cell densities, reflecting greater sensitivity to environmental stress. Although the low-input diet reduced villi height and villus-to-crypt ratio, it tended to increase CD3+ cell density. These effects may be ascribed to the replacement of soybeans with fava beans and their antinutritional factors. These findings highlight the resilience of local breeds to dietary changes, supporting their suitability for alternative poultry production systems.